Inheritance Rights of Children Out of Wedlock in the Perspective of Islamic Law - Sri Istiawati; Yusriana; Deliani; Saniah (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2021)
The aims of study are to find out Inheritance Rights of Children Out of Wedlock in the Perspective of Islamic Law. This study use qualitative research. The result in this study shows that Pregnancy out of wedlock will have a huge psychological impact on the child. The child will be ostracized in the midst of society and there will be tremendous confusion when he grows up to marry because it may be without his biological parents, especially his father, attending.